HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP KELUARGA DALAM PERTOLONGAN PERTAMA KEGAWATDARURATAN DI PUSKESMAS ANDALAS PADANG - Mona ariestia (Jurnal Ilmiah Cerebral Medika, 2023)
Knowledge and attitude are a form of application of understanding and willingness to act, an effort to increase family understanding in emergency cases at home with family emergency first aid as the spearhead of the success of subsequent care as the focus of information provided. The purpose of this study was to determine the relationship between knowledge and family attitudes in emergency first aid in Puskesmas Andalas. The design of this research was correlational analytic with a cross-sectional approach, the number of respondents was 375 people, the sampling technique was consecutive sampling, the instrument used is a questionnaire, the technical data collection was direct with health protocols and using google from a questionnaire. Tests using the Spearman Rho test obtained the Spearman P value = 0.291, which means the value is smaller than p < 0.05 meaning H0 is rejected. It shows that there is a significant relationship between knowledge and family attitudes in emergency first aid in the Sungai Alat village, Astambul District. Families are expected to have good knowledge of helping family members and a fast and appropriate attitude in performing first aid on family members who experience emergency cases.